Ewing sarcoma – pathomechanisms, standard treatment and new therapeutic perspectives - Wojciech Zezuliński; Filip Woliński; Julia Zyśk; Mateusz Korga; Jakub Klas; Jacek Baj; Eliasz Dzierżyński (Quality in Sport)
Introduction: Ewing sarcoma is the second most common bone tumor among children, and due to its high malignancy 5-year survival rate for patients with primary lesions is around 70%. This number drops to merely 30% if metastases are present. Despite combined modality treatment, including radiotherapy, surgery, pre- and post-surgery chemotherapy, the mortality of patients is still too high. This shows a great need to look for new therapeutic options.